Let’s Talk About Money: The Role of Attachment Styles in Couples’ Financial Communication, Financial Management, and Financial Conflict - Monique M. H. Pollmann (Journal of Financial Therapy, 2021)
There are many households with financial problems, but most research on financial management is restricted to individual effects, not taking into account the relationship these individuals are in. The current investigation tests whether a person’s attachment style predicts how comfortable they are talking about financial issues with their partner and how that relates to different financial outcome variables. Two cross-sectional survey studies in the Netherlands and the US, each with more than 100 participants show that a higher score on anxious attachment is related to less communication about money with one’s partner. Less financial communication is related to worse financial management within the couple, which in turn predicts conflicts about money. A third survey with 770 participants shows that less financial communication is related to more financial problems. These findings highlight the need to take relationship variables into account to understand financial processes in couples.
Keywords: communication; attachment styles; financial management; close relationships